Siemens Kulturprogramm: Projekte 1992 : Mit einem Buchauszug 'Siemens Fotoprojekt 1987-1992'. - Weski, Thomas (München : Siemens, 1993)
Gursky, Andreas ; Bonvie, Rudolf ; Koenig, Wilmar ; Adler, Gosbert ; Appelt, Dieter ; Brohm, Joachim ; Feldmann, Hans-Peter ; Fischer, Roland ; von Gagern, Verena ; Gelpke, André ; Görlich, Ulrich ; Horlitz, Andreas ; Hütte, Axel ; Mende, Hans W. ; Schmidt, Michael ; Stamm, Hermann ; Weski, Thomas ; Wunderlich, Petra
Siemens Kulturprogramm: Projekte 1992 /The Siemens Cultural Programme 1992. Together with a travelling exhibition that will be displayed in various constellations at different museums, this book is intended to present the artistic dimension of the project to the general public. The first location where the exhibition is on display will be the Neue Pinakothek, Munich, in May and June 1993 (30.04. - 27.06.1993), followed by the Sprengel Museum Hannover, until September.
boek